A scalable hybrid MAC strategy for traffic-differentiated IoT-enabled intra-vehicular networks - Rahman, Md. Arafatur; A. Taufiq, Asyhari; Ibnu Febry, Kurniawan; Ali, Md Jahan; M. M., Rahman; Karim, Mahima (Elsevier, 2020)
The increasing popularity of Internet of Things-enabled Intra-Vehicular Wireless Sensor Networks (IoT-IVWSNs) relying on IEEE 802.15.4 standard has generated a massive amount of wireless data traffic and put a great pressure in the network functionalities. Along this trend, the existing medium-access control (MAC) protocol struggles to keep up with the unprecedented demand of vehicle monitoring sensors simultaneously emitting data, which can lead to packet collisions, severe network congestion and lost of time-critical data, due to the inflexible characteristics of the protocol. In order to mitigate these issues, this work proposes an enhanced MAC scheme that is scalable to account for diverse sensor-traffic quality of services. The hybrid scheme aims to effectively combine two procedures, namely history- and priority-based MAC, to allocate appropriate network resources for smooth transmission flow from multiple sensors. History-based MAC exploits historical contention data to optimize a near-future contention window that aims to minimize packet collision and expedite the average data delivery. Priority-based MAC assigns priority based on the time-criticality of the sensing data, which is subsequently being used to schedules network resources. Numerical results show the desirable performance of the hybrid scheme for IoT-IVWSNs in comparison to the existing MAC and sole history-based or priority-based strategies in the context of packet delivery ratio and transmission delay.